Becoming the Idol: Quantitative Content Analysis of KPopfication in Clash of Champion Casts - Pramesthi, Jasmine Alya (Jurnal PIKMA : Publikasi Ilmu Komunikasi Media Dan Cinema, 2025)
This study employs a quantitative content analysis method to explore the phenomenon of KPopification in the context of Clash of Champion casts, a student competition organized by Ruang Guru. Although the casts are not K-Pop idols, an analysis of 300 tweets reveals that social media audiences often apply K-Pop culture's terms and norms to them. By analyzing the frequency of keywords such as "Trainee," "Maknae," and "Disband," this research identifies audience perception patterns that view participants through the lens of K-Pop culture. The findings reveal that KPopification does not only occur within K-Pop fan communities but can also emerge among general audiences who adopt the K-Pop framework to evaluate individuals outside that context. From the perspective of Social Identity Theory, the casts’ social identities are externally shaped by the audience, creating expectations and pressures that may conflict with the participants' authentic identities. This study provides significant contributions to the field of communication studies, particularly concerning social media and identity formation, by revealing that KPopification can broadly occur beyond traditional fan communities, influencing how individuals are perceived and treated in the digital public sphere.